2016
DOI: 10.9781/ijimai.2016.3710
|View full text |Cite
|
Sign up to set email alerts
|

Spiking Activity of a LIF Neuron in Distributed Delay Framework

Abstract: -Evolution of membrane potential and spiking activity for a single leaky integrate-and-fire (LIF) neuron in distributed delay framework (DDF) is investigated. DDF provides a mechanism to incorporate memory element in terms of delay (kernel) function into a single neuron models. This investigation includes LIF neuron model with two different kinds of delay kernel functions, namely, gamma distributed delay kernel function and hypo-exponential distributed delay kernel function. Evolution of membrane potential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“… is taken ranging from 0.01 to 0.3 with step-size of 0.01 [7], [8]. Spike rate for LIF model in EDD is similar to that of LIF model with stochastic input at small  and reduces in LIF model in EDD is slowly than LIF model with stochastic input for increment in  as shown in Fig.…”
Section: Parameter Valuementioning
confidence: 96%
See 3 more Smart Citations
“… is taken ranging from 0.01 to 0.3 with step-size of 0.01 [7], [8]. Spike rate for LIF model in EDD is similar to that of LIF model with stochastic input at small  and reduces in LIF model in EDD is slowly than LIF model with stochastic input for increment in  as shown in Fig.…”
Section: Parameter Valuementioning
confidence: 96%
“…The aggregated effect of these ions and molecules can be captured in term of stochastic current. Thus, the rate of change of membrane potential ( () Vt) for LIF model with stochastic input stimulus is defined as [5], [6], [7], [10].…”
Section: Distributed Delay Framework Of Neuron Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…al. [30] has shown that "the distributed delay has no effect on stationary state membrane potential distribution of a LIF neuron". In addition, we say that the distributed delay has no effect on steady state solution of the threshold based linear neuron models.…”
Section: Phase Plane Analysismentioning
confidence: 99%